EXPLORING I-YOU INDEXICALS IN GHANAIAN CHURCH MUSIC - Dwamena, Daniel Ofosu; Gyimah Manu, James; Freitas, Philip Kwame (LLT Journal: A Journal on Language and Language Teaching, 2023)
Indexicals are important to contextual inference and generally, in semantic interpretation (Hanks, 1999). The present study set out to examine the use of the I-You indexical pronouns in Ghanaian Church Music. It was revealed that the I-Y spheres of the indexicals received relative frequencies of 4.55% and 3.35% in the data. Again, the study showed various referents of the I-You indexicals and their implication in the data based on their contextual and co-textual cues. The study extends knowledge on the subject of indexicality.